Cadinane sesquiterpenoids of Phomopsis cassiae, an endophytic fungus associated with Cassia spectabilis (Leguminosae) - Silva, Geraldo Humberto; Teles, Helder Lopes; Zanardi, Lisineia Maria; Marx Young, Maria Claudia; Eberlin, Marcos Nogueira; Hadad, Renato; Pfenning, Ludwig H.; Costa-Neto, Claudio Miguel; Castro-Gamboa, Ian; Bolzani, Vanderlan da Silva [UNESP]; Araujo, Angela Regina (Elsevier B.V., 2006)
Five cadinane sesquiterpenes derivatives were isolated by bioassay-guided fractionation from Phomopis cassiae, an endophytic fungus isolated from Cassia spectabilis. The structures of the two diastereoisomeric 3,9,12-trihydroxycalamenenes (1, 2); 3,12-dihydroxycalamenene (3); 3,12-dihydroxycadalene (4) and 3,11,12-trihydroxycadalene (5) were established on the basis of analyses of ID and 2D NMR and HRTOFMS experiments. Antifungal activity of the isolates was evaluated against Cladosporium sphaerospermum and Cladosporium cladosporioides, revealing 5 as the most active compound. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Phomopsis; endophytic fungi; Cadinane Sesquiterpenes; antifungal